Ambient particulate matter exposure and cardiovascular diseases: a focus on progenitor and stem cells. Issue 5 (14th March 2016) - Cui, Yuqi; Sun, Qinghua; Liu, Zhenguo
Abstract: Air pollution is a major challenge to public health. Ambient fine particulate matter (PM) is the key component for air pollution, and associated with significant mortality. The majority of the mortality following PM exposure is related to cardiovascular diseases. However, the mechanisms for the adverse effects of PM exposure on cardiovascular system remain largely unknown and under active investigation. Endothelial dysfunction or injury is considered one of the major factors that contribute to the development of cardiovascular diseases such as atherosclerosis and coronary heart disease. Endothelial progenitor cells (EPCs) play a critical role in maintaining the structural and functional integrity of vasculature. Particulate matter exposure significantly suppressed the number and function of EPCs in animals and humans. However, the mechanisms for the detrimental effects of PM on EPCs remain to be fully defined. One of the important mechanisms might be related to increased level of reactive oxygen species (ROS) and inflammation. Bone marrow (BM) is a major source of EPCs. Thus, the number and function of EPCs could be intimately associated with the population and functional status of stem cells (SCs) in the BM. Bone marrow stem cells and other SCs have the potential for cardiovascular regeneration and repair. The present review is focused on summarizing the detrimental effects of PM exposure on EPCs and SCs, and potential mechanisms including ROS formation as well as clinical implications.